Regenerative medicine improve neurodegenerative diseases - Ashraf, Seyedeh Sara; Hosseinpour Sarmadi, Vahid; Larijani, Ghazaleh; Naderi Garahgheshlagh, Soheila; Ramezani, Sara; Moghadamifar, Soraya; Mohebi, Seyedeh Lena; Brouki Milan, Peiman; Haramshahi, Seyed Mohammad Amin; Ahmadirad, Nooshin; Amini, Naser (Cell and tissue banking, 2023)
Regenerative medicine is a subdivision of medicine that improves methods to regrow, repair or replace unhealthy cells and tissues to return to normal function. Cell therapy, gene therapy, nanomedicine as choices used to cure neurodegenerative disease. Recently, studies related to the treatment of neurodegenerative disorders have been focused on stem cell therapy and Nano-drugs beyond other than regenerative medicine. Hence, by data from experimental models and clinical trials, we review the impact of stem cell therapy, gene therapy, and nanomedicine on the treatment of Alzheimer’s disease (AD), Parkinson’s disease (PD), and Amyotrophic lateral sclerosis (ALS). Indeed, improved knowledge and continued research on gene therapy and nanomedicine in treating Alzheimer's disease, Parkinson's disease, and Amyotrophic lateral sclerosis lead to advancements in effective and practical treatments for neurodegenerative diseases.